1984, de George Orwell : uma leitura a partir da teoria crítica da sociedade - Grobério, Júlia Bragatto (2024)
This work intends to answer how the dystopia 1984, written by George Orwell, can contribute to readers' ability to understand, beyond the surface, contemporary social phenomena. The objective of the research was to reflect on the role of the dystopia literary genre in the formation of critical readers. The hypothesis constituted is that the dystopia literary genre, even if written more than seventy years ago, as is the case in 1984, when describing social organizations characterized by intolerable living conditions, manages to criticize trends in current society, as it invites readers to broaden their reflection on contemporary social phenomena. The methodology is based on a qualitative research perspective, with an interpretative analysis of the book 1984, by George Orwell, based on concepts such as spectacle society and cultural industry, based on dialogue with the tradition of critical theory of society, inaugurated by the Frankfurt Institute for Social Research